Adherence to highly active anti-retroviral treatment (HAART) and its associated factors among HIV-positive patients in Sungai Buloh Hospital, Malaysia / Umar Yagoub Mohammed Yousif - Yousif, Umar Yagoub Mohammed (2012)

(untitled)
HIV/AIDS is one of the most destructive health diseases of modern times, affecting approximately 45.5 million people worldwide. But the advent of the Highly Active Antiretroviral Therapy (HAART) in 1996 has significantly reduced HIV/AIDS-related mortality and morbidity and it has allowed many previously bed-ridden patients to live healthier and more productive lives. In order for the treatments to be successful, a very high level of adherence to HAART is required. It is estimated that at least 95% adherence to antiretroviral treatment is essential to reduce the replication of the virus and prevent the development of resistance to treatment. Generally, adherence is considered to be a complex clinical behaviour with a wide array of determinants. Thus, the aim of this study is to assess the level of adherence to HAART among HIV/AIDS-positive patients in a major hospital in Malaysia as well as its determinants. Using prospective cohort study design, 925 participants who were on antiretroviral treatment were selected for the purpose of this study. Inclusion and exclusion criteria were also applied. The following three instruments for measuring the level of adherence to HAART were used in this study: self-reported adherence questionnaire, pharmacy refill records and Therapeutic Drug Monitoring (TDM) for testing drug in human plasma. Two blood samples were collected and tested for the presence or absence of three antiretroviral drugs, namely Efavirenz, Nevirapine and Lamivudine in human plasma using the LC-MS/MS machine. A test-retest reliability assessment was performed on a pilot test of 40 HIV/AIDS-positive patients. Three main data analysis techniques were used to analyze the collected data: descriptive analysis, comparative analysis of contingency tables, lastly logistic regression analysis. This is the first study in South East Asia and Malaysia to analyze three antiretroviral treatment using LC-MS/MS machine. It is also the first study in Malaysia to use three different methods for measuring the adherence level to Highly Active Antiretroviral Treatment (HART). The overall adherence level as measured by the self-reported questionnaire was 81.7%. The adherence levels using TDM for Efavirenz, Nevirapine and Lamivudine were 71.2%, 69.6% and 60.3% respectively. Sensitivity was highest for Efavirenz (0.95; 95% CI 0.92, 0.96) and lowest for Lamivudine (0.89; 95% CI 0.85, 0.92). SRA specificity ranged between 0.56 and 0.63 and was highest for Nevirapine. Positive Predictive Value Positive (PPV) for Self-Reported Adherence (SRA) ranged between 0.76 (Lamivudine) to 0.84 (Efavirenz). Overall diagnostic accuracy ranged between 0.76 (Lamivudine) to 0.84 (Nevirapine) while Area Under the Curve (AUC) ranged between 0.76 (Lamivudine) to 0.83 (Efavirenz). In our findings of the logistic regression and cross tabulation analysis, we evaluated 48 variables which can be classified into four groups: reasons for missing medications, factors facilitating adherence, adverse effects of medications and alternative medications used for HIV treatment. Some of the factors associated with adherence include age, income, educational level, marital status, diarrhoea, vomiting, use of Alarm clock, acceptance of HIV status and use of herbal medicine. In conclusion, according to the different methods of comparative analysis, it is evident that self-reported adherence is good enough for measuring adherence level in a poor resource setting and many factors have been found to be associated with adherence level to HAART.